PARADIGMA BARU PENDIDIKAN MENUJU MASYARAKAT MADANI (TELAAH KRITIS TERKADAP PROBLEM PENDIDIKAN NASIONAL, ARAH KEBIJAKAN, DAN STRATEGI PEMECAHANNYA) - Dadan Rosana, Dadan Rosana (Jurnal Cakrawala Pendidikan, 2016)
The educational system and values have developed very fast, urged by the spirit of reformation in various aspects of human life. The demand for the formation of a civil society has made education one very effective way to approach it. For that purpose, there needs to be a change towards a new paradigm which must be followed with a review on the problems of the national education, the direction of its policies, and its strategies of problem solving.